Grain yields of maize and the nitrogen contribution following Stylosanthes pasture in the Nigerian subhumid zone - Mohamed-Saleem, M.A.; Otsyina, R.M. (Cambridge University Press, 1986)
An experiment conducted to study the nitrogen contribution from stylosanthes fodder banks of different ages to succeeding maize crops. Discusses the implications for the development of traditional agro-pastoral production systems.